Inhibition of Myocardial Cell Apoptosis Is Important Mechanism for Ginsenoside in the Limitation of Myocardial Ischemia/Reperfusion Injury - Chen, Zhihan; Wu, Jingping; Li, Sijing; Liu, Caijiao; Ren, Yulan (Frontiers in Pharmacology, 2022)
Ischemic heart disease has a high mortality and the recommended therapy is reperfusion. Nevertheless, the restoration of blood flow to ischemic tissue leads to further damage, namely myocardial ischemia/reperfusion injury (MIRI). Apoptosis is an essential pathogenic factor in MIRI, and ginsenosides are effective in inhibiting apoptosis and alleviating MIRI. Here, we reviewed published studies on the anti-apoptotic effects of ginsenosides and their mechanisms of action in improving MIRI. Each ginsenoside can regulate multiple pathways to protect the myocardium. Overall, the involved apoptotic pathways include death receptors signaling pathway, mitochondria signaling pathway, PI3K/Akt signaling pathway, NF-κB signaling pathway, MAPK signaling pathway, and so on. Ginsenosides, with diverse chemical structures, regulate different apoptotic pathways to relieve MIRI. Summarizing the effects and mechanisms of ginsenosides contributes to further mechanism researches and structure-function relationship researches, which can help the development of new drugs. Therefore, we expect that this review will highlight the importance of ginsenosides in improving MIRI via anti-apoptosis, and provide references and suggestions to further research in this field.